Deutsches Architektur Jahrbuch = German architecture annual. - Schmal, Peter Cachola, editor; Busenkell, Michaela, editor (Frankfurt am Main: Deutsches Architekturmuseum; New York : Prestel Verlag, 2009)
PRZSL